Design of a Dynamometer for High Power Engines - Ibrahem A. Muhsin; Jawad K. Oleiwi (Journal of Engineering and Sustainable Development, 2008)
This study is conducted to design a hydraulic dynamometer to assay a high power engines by employing the tapered land thrust bearing for absorbing engine power. The project is an attempt to design a dynamometer device, which could be used in the libratory of industries. The design work involves a theoretical approach based on finite element analysis for the main parts of this hydraulic dynamometer which are the spline hollow shaft, the tapered–land thrust bearing and selection oil cooling system. The results show that the shaft length = 0.6 m and diameter ratio (Do/Di) =1.5 for outer diameter Do= 0.1524 m with 18–spline teeth which represents the hollow splined shaft. While for the thrust bearing the diameter ratio (do/di) =1.28 for inner diameter di = 0.1778 m and bearing thickness = 4 mm with numbers of bearing pairs = 40 and using oil type VG 22 as lubricant fluid with dynamic viscosity = 13 cp at 50 ْC